THE INFLUENCE OF BRAND AMBASSADOR, COUNTRY AND PRODUCT IMAGE, AND KOREAN WAVE ON BEHAVIOR WITH ATTITUDE AS A MEDIATING VARIABLE FOR CALVIN KLEIN WITH JUNGKOOK BTS AS BRAND AMBASSADOR IN INDONESIA: Pengaruh Brand Ambassador, Country dan Product Image serta Korean Wave terhadap Behavior dengan Attitude sebagai Variabel Mediasi Pada Calvin Klein dengan Jungkook BTS sebagai Brand Ambassador di Indonesia - Zalfa Ulayya Arki; Mike Yolanda (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to analyze the influence of Brand Ambassador, Country and Product Image, and Korean Wave on Behavior with Attitude as a Mediating Variable for Calvin Klein with Jungkook BTS as Brand Ambassador in Indonesia. The population of this research includes consumers who recognize Calvin Klein products and have an interest in Jungkook as a brand ambassador. The sampling technique used in this study is purposive sampling, with a sample size of 200 respondents. Data was collected through the distribution of online questionnaires and processed using SmartPLS 4.1.0.9 software. The results of this study indicate that (1) Brand Ambassador has a positive and significant effect on Country and Product Image for Calvin Klein products in Indonesia, (2) Korean Wave has a positive and significant effect on Country and Product Image for Calvin Klein products in Indonesia, (3) Korean Wave has a positive and significant effect on consumer Attitude towards Calvin Klein products in Indonesia, (4) Country and Product Image have a positive and significant effect on consumer Attitude towards Calvin Klein products in Indonesia, (5) Attitude has a positive and significant effect on consumer Behavior towards Calvin Klein products in Indonesia.